1989
DOI: 10.1002/jez.1402490207
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in coho and chinook salmon resulting from acute insufficiency in pancreatic hormones

Abstract: Acute deficiency in pancreatic peptides (insulin, somatostatin-25, glucagon, and glucagon-like peptide) was invoked for 9-12 hr in coho, Oncorhynchus kisutch, and chinook, O. tshawytscha, salmon by administration of specific antisera raised against purified salmon hormones. Insulin-deficient fish were hyperglycemic, had diminished glycogen content in the liver (Plisetskaya et al., '88a, elevated liver triacylglycerol lipase activity, and higher concentration of plasma triiodothyronine (T3) compared to a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…The action of SSTs are opposite to those of insulin, which is a lipogenic hormone. In salmon treated with anti-SST-25 serum, liver triacylglycerol lipase activity is substantially lowered, while AIS administered in the same experiment elevates lipase activity (Plisetskaya et al 1989b). At this time, it is difficult to decide whether the metabolic effects of salmon SST-25 are direct or indirect.…”
Section: Effects Of Pancreatic Hormones On Fish Growth and Metabolismmentioning
confidence: 94%
“…The action of SSTs are opposite to those of insulin, which is a lipogenic hormone. In salmon treated with anti-SST-25 serum, liver triacylglycerol lipase activity is substantially lowered, while AIS administered in the same experiment elevates lipase activity (Plisetskaya et al 1989b). At this time, it is difficult to decide whether the metabolic effects of salmon SST-25 are direct or indirect.…”
Section: Effects Of Pancreatic Hormones On Fish Growth and Metabolismmentioning
confidence: 94%
“…These data are consistent with those for hagfish, another cyclostome, in which INS insufficiency 24 hr after guinea pig anti-human INS serum administration resulted in a decline of plasma T 3 levels (Plisetskaya et al ., 1983). In contrast, salmon had a higher concentration of plasma T 3 12 hr after the administration of anti-salmon INS serum (Plisetskaya et al ., 1989). This suggests that the mechanism of TH regulation by INS in teleosts and cyclostomes is fundamentally different.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve to 14 hr after the last injection, individual animals were anesthetized with 0.05% tricaine methanesulfonate. Acute neutralization of pancreatic hormones was induced essentially as previously described by Plisetskaya et al (1989). Groups of 10 larvae received an intraperitoneal injection of 10 µ l/g body weight of 1:1 mixture of 0.6% saline and either anti-lamprey INS or normal rabbit serum (control).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, the results are often contradictory. Several studies have suggested the anti-lipolytic effect of insulin (Harmon and Sheridan, 1992;Plisetskaya et al, 1989) and an insulin-induced increase of lipid storage in many fish (Cowley and Sheridan, 1993;Plagnes-Juan et al, 2008;Ellesat et al, 2011). In contrast, some authors found that this pathway remained unaffected by insulin (Plagnes-Juan et al, 2008;Warman and Bottino, 1978).…”
Section: Introductionmentioning
confidence: 99%